2011
DOI: 10.1007/s00216-011-5503-4
|View full text |Cite
|
Sign up to set email alerts
|

Condensation cascades and methylgroup transfer reactions during the formation of arsane, methyl- and dimethylarsane by aqueous borohydride and (methyl) arsenates

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Condensation cascades and methylgroup transfer reactions during the formation of arsane, methyl-and dimethylarsane by aqueous borohydride and (methyl) arsenates D'Ulivo, Alessandro; Meija, Juris; Mester, Zoltán; Pagliano, Enea; Sturgeon, Ralph E.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The binomial distribution originates from the multistep hydrogen transfer, as outlined for diarsane in Figure 4. The trends observed in the composition of diarsane and triarsane follow the hypothesis of a concerted multistep formation of arsane in a fashion already demonstrated for AsH 3 [11], and they further validate the proposed condensation cascade mechanism [14]. Therefore, the formation of di-and triarsanes can be described as a combination of two independent events: condensation of two hydroxoarsanes and their reduction by borohydrides via the concerted transfer of hydrogen to the arsenic substrate, as summarized in Scheme 1.…”
Section: Mechanism Of Formation Of Polyarsanessupporting
confidence: 82%
See 2 more Smart Citations
“…The binomial distribution originates from the multistep hydrogen transfer, as outlined for diarsane in Figure 4. The trends observed in the composition of diarsane and triarsane follow the hypothesis of a concerted multistep formation of arsane in a fashion already demonstrated for AsH 3 [11], and they further validate the proposed condensation cascade mechanism [14]. Therefore, the formation of di-and triarsanes can be described as a combination of two independent events: condensation of two hydroxoarsanes and their reduction by borohydrides via the concerted transfer of hydrogen to the arsenic substrate, as summarized in Scheme 1.…”
Section: Mechanism Of Formation Of Polyarsanessupporting
confidence: 82%
“…The stoichiometry of the above reaction is respected only when arsenic compounds are present at trace levels in an excess of boranes (i.e., under analytical conditions). When the concentration of arsenic rises above the millimolar level, however, a complex set of side reactions takes place [14] with formation of condensation products:…”
Section: Mechanism Of Formation Of Polyarsanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Wu et al 122 review the application of several reducing systems other than tetrahydroborate; while D'Ulivo et al 126 discuss the mechanisms of hydrides forming from iAs and from methylated arsenic species, by using NaBH 4 and the formation of intermediate by-products. Anawar 127 discusses the advantages and disadvantages of the combined HG-ETAAS system, in a review focused on this combined technique applied to arsenic speciation.…”
Section: Techniques Involving Hydride Generation (Hg) As a Derivatizamentioning
confidence: 99%
“…More recently, further mass spectrometric evidences [9][10][11] on arsane and methylarsane generation showed that approaching the low THB/analyte ratio, typical of "synthetic-like" conditions, several polymeric arsanes could be identified both in vapor and liquid phase and precipitation of a large mass fraction of the analyte is observed at the higher analyte concentrations employed. In the case of lead this effect could be also magnified by the change of structure of lead substrates reacting with THB, in view of the significant change of speciation of aqueous lead ions passing from micromolar to millimolar level total lead ( Fig.…”
mentioning
confidence: 99%